Cyberhate: Profiling of Potential Targets - Garbutt, Malcolm (2020)
Cyberhate is defined as hatred expressed in online environments directed at groups and individuals based on their race, religious belief, ethnic origin, sexual orientation, or gender. Cyberhate is a growing phenomenon, as it coincides with increased access to the Internet. This paper explores cyberhate awareness, observations, and experiences to present a profile of cyberhate victims using the Routine Activities Theory. Providing such a profile can raise awareness of at-risk targets and provide opportunities for intervention. A survey of 183 students at a large university provided insight into online user experiences. The research revealed links between awareness, observations, and experiences of cyberhate on various online platforms. While awareness of cyberhate was associated with frequent Internet and social media access, reported experiences of cyberhate were lower than anticipated. Males experienced higher levels of cyberhate in online games and news sites. Likewise, older students experienced higher levels of cyberhate on news sites, as did respondents with higher education levels who also experienced a higher level of cyberhate on chat sites. Daily users of social media experienced higher levels of cyberhate on such platforms. An interesting finding was a correlation between frequent online gaming and lower levels of empathy for victims. The findings show the complexity of defining a profile for cyberhate targets